Caracterização e análise da localização das instalações logísticas para entrega urbana em Belo Horizonte - Gabriela Pereira Lopes (2018)
City logistics can be defined as the goods’ flow management inserted in the complexity of cities. One of the causes of this complexity is the accelerated urbanization process, which, together with insufficient public policies, has made consequences for urban mobility. The urban goods distribution is essential for the functioning of the cities; however, historically low attention has been paid to this activity in academic and political areas. In this context, this work determined the warehouse freight trip generation model to support the development of public policies that guide the location of these logistics facilities. For that matter, a survey was conducted which collected information about morphological-functional characteristics and factors that influence the current position of the warehouses. Beyond the freight trip generation model, the spatial correlation of the location of warehouses and destinations of deliveries (i) with demographic and socioeconomic data being analyzed; and (ii) with land use. The results showed that 78% of the warehouses in Belo Horizonte are located up to 5 km from the Celso Mello Azevedo Highway Ring. This preference is due to the road infrastructure easy access, both at the goods time of arrival and at the of urban distribution time, the latter being the most significant factor, given that distributors are primarily concerned with this stage. The facilities costs have a more significant impact on the warehouse's location compared to the proximity to the consumer market. However, the consumer market proximity is considered for these logistics facilities location definition. The results also indicate that 62% of the warehouses do not internalise the impacts related to loading and unloading operations, and 83% do not internalise the impacts associated with the parking of the individual transport vehicles attracted to the logistics facilities. In this way, it is essential for public authorities to license these enterprises, avoiding micro-localisation of warehouses and allowing the adoption of projects with the internalization of their negative impacts.